The Improved Sand characterization of Mafe Field of Niger Delta by integrated well logs information and 3D seismic data - Okpogo, Emele Uduma; Atueyi, Ifeyinwa Obiageli; Abbey, Chukwuemeka Patrick (Iraqi Journal of Science, 2018)
Well log rock physics and seismic facies analysis was carried out with a view to enhancing reservoir sand characterization of Mafe Field of Niger Delta. Lithofacies were identified using suites of well logs and correlated across the block. Rock properties were estimated from wireline logs using empirical methods. Vp-porosity crossplot was used to characterize the delineated sandstone reservoirs by comparing observed clusters and trends with various rock physics models. Seismic attribute analysis was employed to detect lateral changes in lithology across the field. Reservoir A is a relatively clean sand, with low average volume of shale of 0.4, average thickness of 55m, good average porosity of 0.26 and average water saturation of 0.45. Reservoir B is also a relatively clean sand with low average volume of shale of 0.35, average thickness of 85m, high average porosity of 0.27 and average water saturation of 0.54. Reservoir C has an estimated volume of shale of 0.21 average total porosity of 0.23, and an average thickness of 70m with average water saturation of 0.65. Reservoir A conforms to the friable sand model while Vp-porosity crossplot cluster trend for both reservoir B and C show trend and properties imitating the contact cement model. The time slices extracted at different time intervals from the envelope and instantaneous frequency cubes show lateral variation in lithofacies across the delineated sandstones. Instantaneous frequency decreases from southwest to northeast which corresponds to decrease in shalines. Reservoir quality information can be predicted or even derived from the estimated petrophysical properties since these parameters such as porosity and volume of shale are sometimes closely associated with rock properties such as sorting, lithofacies and grain maturity.